Relationship sport motivation and sportsmanship behaviour among SUKIPT athlete / Ummi Amanina Humaidi - Humaidi, Ummi Amanina (2018)
The study aims to examine relationship between sport part1c1pation and sportsmanship behavior among university students. The method that were used in this study was descriptive research which was a type of quantitative research. The sample of this study were randomly selected of subject that had been used was based on the number of sample from SUKIPT athletes. The study was included 440 athletes from 8000 athletes, age 18-28 years old as the sample. The queationaire were used in this study was Sport Motivation Scale (SMS) and Multidimensional Sportsperson Orientation Scale (MSOS). This researcher were utilize different analyses, which is descriptive analysis method and Pearson's correlation and Independent t-Test in terms of gender between genders sports motivation and sportsmanship behaviour. There is significant difference of sport motivation and sportsmanship behaviour among SUKIPT athletes. There is also significant relationship between sport motivation and sportsmanship behaviour among SUKIPT athlete. In conclusion, this study indicated that sport motivation and sportsmanship behaviour among SUKIPT athletes has relationship. These shown that by recognize the personality of youth athlete based on their motivation whether intrinsic or extrinsic to be sportsperson and high level in sportsmanship behavior. Sometimes different athletes have a different characteristic to shown in filed or game sport.